2016
DOI: 10.1016/j.joca.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of human plasma reveals that arginine is depleted in knee osteoarthritis patients

Abstract: Arginine is significantly depleted in refractory knee OA patients. Further studies within a longitudinal setting are required to examine whether arginine can predict early OA changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 35 publications
(39 reference statements)
10
92
3
Order By: Relevance
“…Metabolic profiling using synovial fluid collected from 55 knee OA patients and 13 cadaveric controls, revealed 11 metabolites that separated the two groups 41 . None of the 11 metabolites identified in synovial fluid matched those found in the urine samples from our progression study or those found in plasma samples from a cross-sectional study of knee OA 20 .…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Metabolic profiling using synovial fluid collected from 55 knee OA patients and 13 cadaveric controls, revealed 11 metabolites that separated the two groups 41 . None of the 11 metabolites identified in synovial fluid matched those found in the urine samples from our progression study or those found in plasma samples from a cross-sectional study of knee OA 20 .…”
Section: Discussioncontrasting
confidence: 71%
“…All prior metabolomic studies in humans have been cross-sectional in nature comparing individuals with or without OA using either urine 18, 40 , serum 19 , synovial fluid 41 or plasma 20 . An NMR-based urine metabolomics study that used samples from the Johnston County Osteoarthritis project found differences in participants with radiographic hip or knee OA from controls and noted a correlation of a metabolite profile with radiographic OA severity 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this study, arginine levels were initially identified as decreased following treatment at the earliest time point. A recent study of human plasma also identified arginine to be depleted in knee OA 75 . The authors proposed this is due to an increased activity of the conversion of arginine to ornithine resulting in an imbalance between cartilage repair and degradation.…”
Section: Discussionmentioning
confidence: 94%